Leg length discrepancy and adolescent idiopathic scoliosis: clinical and radiological characteristics (Sept, 10.1007/s43390-021-00417-0, 2021) - Büyükaslan, Ahsen; Abul, Kadir; Berk, Haluk; Yılmaz, Hürriyet (Springer, 2022)
The original version of this article unfortunately contained a mistake. In Fig.
Correction to: Leg length discrepancy and adolescent idiopathic scoliosis: clinical and radiological characteristics (Spine Deformity, (2022), 10, 2, (307-314), 10.1007/s43390-021-00417-0)
Keywords: Leg Length Discrepancy; Leg Length Discrepancy Scoliometer Test; Pelvic Obliquity; Scoliosis